(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article presents an analysis of Burkhoniddin Marginoniy’s works on Islamic jurisprudence (fiqh), the significance of the rule of law in ensuring the spiritual stability of society, and a systematic analysis of socio-ethical norms such as equality, duty, inheritance, peace, prosperous living, and public education.